STEM leaders promoting resilience within equity-centered K-12 STEM education organizations - Marshall, Stefanie L.; Galey-Horn, Sarah (Frontiers in Education, 2024)
Introduction This study examines storytelling’s role in supporting organizational resilience for equitable STEM instruction by schools and districts. Within K-12 organizations, some practices may be perceived as mundane, but storytelling supports transformation toward achieving equitable STEM learning opportunities in a school. Therefore, storytelling is a means for achieving organizational resilience. Methods Through a comparative case study design, this paper explores challenges identified by educational leaders through focus groups who worked with teams to activate interdisciplinary learning to support thriving STEM programming to enhance equitable science instruction. Results We characterize STEM systems’ social and organizational phenomena from three educational contexts. We start by sharing these systems’ backgrounds and educational goals, with specific attentiveness to their STEM programming. We then share the stories told by their leaders to promote organizational resilience (these characteristics, as previously described, are italicized throughout this section) within each of the given contexts. Discussion The STEM stories in this study shared the state of STEM within a school and district, the instructional mission of STEM, and a community STEM story.